The Islam Defence Action: A Challenge of Islamic Movement to Democratic Transition in the Post 2014 Indonesia - Ari Ganjar Herdiansah; Dian Arifiyati Putri; Latip Ashari; Rini Maduratmi (Sekolah Pascasarjana Universitas Brawijaya, 2017)
The Islam Defense Action in Jakarta during November to December 2016 was the largest protest movement that ever been held in Indonesia and brought national concerns over political instability. Hudred thousands to milions of people overwhelmed the streets protesting the alleged blasphemy on Islam by Basuki Tjahaja Purnama, a candidate for the 2017 Jakarta gubernatorial election that has a close connection to President Joko Widodo. This article analyzes the outbreak of the protest movement as a depiction of the strategic influence of Islamic groups in the midst of political upheaval threat. The protest movement showed a struggle to defend their values, but on the other hand its political impact cannot be disclaimed. Above all of the phenomena, Islam Defense Action implies that religious sentiment still interacts with the politics and challenging the role of Islamic civil society toward Indonesia democracy transition in the post 2014.